2018
DOI: 10.11604/pamj.2018.31.25.13665
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans: clinicopathologic presentation in Nigerians

Abstract: IntroductionDermatofibrosarcoma protuberance (DFSP) is in general a rare low grade malignant sarcoma and possesses a tendency for local recurrence. It has a site predilection for the trunk. Occurrence in the facial area is extremely rare. Ample knowledge of its clinical, histological and biologic characteristics is vital for accurate and prompt recognition.MethodsOver 13 years, clinicohistologic information of cases was retrieved. Histological and immunohistochemical re-evaluation were performed to re-confirm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…This present study has shown a recurrence following 20 years after primary tumour resection and this may be one of the longest duration so far reported in literature with a few reporting 10 years [ 8 ], while cases showing recurrence few weeks after resection has also been documented [ 8 ]. Patients could therefore be expected to develop recurrence beyond the recommended follow up interval [ 6 ].We believe that this study is one of the few to report male predominance [ 5 ] compared to most studies reporting more cases in females [ 3 , 4 , 8 , 10 ], with a study in Nigeria showing equal gender incidence [ 7 ]. Another study that reported male predominance considered only acral site tumours, hence, the study may not be representative of all cases seen in that population.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…This present study has shown a recurrence following 20 years after primary tumour resection and this may be one of the longest duration so far reported in literature with a few reporting 10 years [ 8 ], while cases showing recurrence few weeks after resection has also been documented [ 8 ]. Patients could therefore be expected to develop recurrence beyond the recommended follow up interval [ 6 ].We believe that this study is one of the few to report male predominance [ 5 ] compared to most studies reporting more cases in females [ 3 , 4 , 8 , 10 ], with a study in Nigeria showing equal gender incidence [ 7 ]. Another study that reported male predominance considered only acral site tumours, hence, the study may not be representative of all cases seen in that population.…”
Section: Discussionmentioning
confidence: 91%
“…The rarity of DFSP is shown by the small number of cases reported in various studies from different parts of the world, some of which span more than two decades [ 6 , 7 , 10 ]. This current study is another report in that regard.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations